Product Lifecycle Management (Volume 1) 21st Century Paradigm for Product Realisation - Stark, John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This fifth edition of (3z(BProduct Lifecycle Management(3y (Bupdates and adds to the successful fourth edition, the most frequently cited PLM publication. It gives the reader a thorough explanation of Product Lifecycle Management (PLM) and provides them with a full understanding and the skills to implement PLM within their own business environment. This new and expanded edition is fully updated to reflect the many technological and management advances made in PLM since the release of the fourth edition. (3z(BProduct Lifecycle Management(3y (Bwill broaden the reader$1 (Bs understanding of PLM, nurturing the skills needed to implement PLM successfully and to achieve world-class product performance across the lifecycle. Among the components of PLM described are product-related business processes, product data, product data management (PDM) systems, other PLM applications, best practices, company objectives and organisation. This book also describes the relationships of PLM with the Internet of Things, Industry 4.0, Digital Twins and Digital Threads. (3z(BProduct Lifecycle Management(3y (B(5th edition) explains what PLM is, and why it is needed. It describes the environment in which products are ideated, developed, manufactured, supported and retired, before addressing the main components of PLM and PLM Initiatives. Key activities in PLM Initiatives described include organisational change management (OCM) and project management. The final part of the book addresses the PLM Initiative, showing the typical steps and activities of a PLM project or initiative.s
Product Lifecycle Management -- PLM and its Surroundings -- PLM and Products -- PLM and Business Processes -- PLM and Product Data -- PLM and PDM -- PLM and Product-Related Applications -- PLM, Techniques and Methods -- PLM and the Internet of Things and Industry 4.0 -- PLM, Digital Twin and Digital Thread -- PLM and Organisational Change Management -- PLM and Project Management -- PLM and Executives -- PLM and the PLM Initiative -- PLM in Industry.
Keywords: Industrial engineering; Production engineering; Operations research; Engineering design; Cooperating objects (Computer systems).; Project management; Industrial and Production Engineering; Operations Research and Decision Theory; Engineering Design; Cyber-Physical Systems; Project Management; Product management; Product life cycle